Binding specificity of type three secretion system effector NleH2 to multi‐cargo chaperone CesT and their phosphorylation. (19th November 2021) - Yadav, Manisha; Srinivasan, Mahalashmi; Tulsian, Nikhil K.; Liu, Yu Xuan; Lin, Qingsong; Rosenshine, Ilan; Sivaraman, J.
Abstract: Gram‐negative pathogens like Enteropathogenic Escherichia coli (EPEC) utilize the type three secretion system (T3SS) to translocate various effector proteins that are needed to "hijack" the host system for pathogenic survival. Specialized T3SS chaperones inside bacterial cells stabilize these effector proteins and facilitate their translocation. CesT is a unique multi‐cargo chaperone that interacts with and translocates 10 different effector proteins. Here, we report the specific interaction between CesT and its key effector, NleH2, and explore the potential role of NleH2 as a kinase for CesT phosphorylation. First, we identified the chaperone‐binding domain (CBD; 19–97aa) of NleH2, and mapped the specific interaction sites for both CesT and NleH2. The N‐ and C‐terminal residues of the CBD interact with the dimeric interface of CesT. Further, we compared the CesT binding to NleH2, to that of another key effector Tir and with the global carbon regulator CsrA. Notably, the effectors have the binding regions at the β‐sheet core and dimer interface of CesT, whereas the CsrA regulator interacts predominantly through the C‐terminal region, which is found 17 Å away from the effectors‐binding sites. Next, we showed that NleH2 remains an active kinase even as a complex with CesT and is responsible for its autophosphorylation as well as phosphorylation of CesT at Tyr153. Collectively, our findings enhance the understanding of the role of multi‐cargo chaperone CesT in orchestrating effector translocation through T3SS.